Evaluating drug distribution in children and young adults with diffuse midline glioma of the pons (DIPG) treated with convection-enhanced drug delivery - Szychot, Elwira; Bhagawati, Dolin; Sokolska, Magdalena Joanna; Walker, David; Gill, Steven; Hyare, Harpreet (Frontiers in Neuroimaging, 2023)
There is currently no method for evaluating drug distribution and tumour coverage using the convection-enhanced drug delivery (CED) technique in diffuse midline glioma of the pons (DIPG). AIMS: To determine an imaging protocol that can be used to assess the distribution of infusate in children with DIPG treated with CED. METHODS: 13 children diagnosed with DIPG received between 3.8–5.7ml of infusate, through 2 pairs of catheters to encompass tumour volume on day 1 of cycle 1 of treatment. Volumetric T2-weighted (T2W) and diffusion-weighted MRI imaging (DWI) were performed before and after day 1 of CED. Apparent diffusion coefficient (ADC) maps were calculated. The tumour volume pre and post CED was automatically segmented on T2W and ADC on the basis of signal intensity. The ADC maps pre and post infusion were aligned and subtracted to visualize the infusate distribution. RESULTS: There was a significant increase (p<0.001) in mean ADC and T2W signal intensity (SI) ratio and a significant (p<0.001) increase in mean tumour volume defined by ADC and T2W SI post infusion (mean ADC volume pre: 19.8ml, post: 24.4ml; mean T2W volume pre: 19.4ml, post: 23.4ml). A significant correlation (p<0.001) between infusate volume and difference in ADC/T2W SI defined tumour volume was observed (ADC, r=0.76; T2W, r=0.70). Finally, pixel-by-pixel subtraction of the ADC maps pre and post infusion demonstrated a volume of high signal intensity, presumed infusate distribution. CONCLUSIONS: ADC and T2W MRI are proposed as a combined parameter method for evaluation of CED infusate distribution in brainstem tumours in future clinical trials.